IMPLEMENTASI KEBIJAKAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDes) UNTUK MENINGKATKAN PEMBANGUNAN DESA (Studi Kasus di Desa Bandung Kecamatan Gedeg Kabupaten Mojokerto) - Selamet Joko Utomo (Trunojoyo University of Madura, 2015)
This study analyzes the implementation of policies APBDes in improving rural development. In APBDes policy implementation is often in its execution is still a dominance of village government. APBDes policies should apply the principle of good governance that include participation, transparency and accountability so that the goal is done in village development can be achieved. Qualitative descriptive analysis techniques using domain analysis technique which uses the pattern of semantic relationships. The results show, that in the process of policy implementation APBDes held in the village of Bandung has not met the principles of Good Governance. In terms of community participation, the community has not been involved in policy-making process of development and community participation has not been instituted so that people do not have the power to influence policy-making, in terms of transparency, the village government is not open to the public in the financial management of the village where the people do not have access to know the size budget managed by the village government. In terms of accountability, accountability of village government in its financial management was limited to formal legal qualifies only, and not be accountable to the village where the government is accountable for the implementation of its development to the people they lead.